ONTOLOGICAL - METAPHYSICAL SPECIFICITY OF ACTIVITY - Baranov, Gennady (Revista Inclusiones, 2020)
The article aims to theoretically substantiate the onto-metaphysical hypothesis about the essence and specificity of activity in the attribute state of the anti-chaotic realization of a united infinite being and its autonomous part (object). The application of the methodological tools used in the article (the ontological approach, the principle of pluralism, the comparative method, the logical methods of abstraction and deduction) made it possible to abstract from the value criteria in the study of the essence of activity and its attributive specifics and focus on the analysis of the ontological anti-chaos specificity of activity. The article reveals the attributive specificity of activity in the state of anti-chaotic realization of being. The anti-chaotic realization of being is characterized by a variety of activity implementations, but not by a separate priority class of change, in particular, an activity class. In the system of ontology concepts, activity by logical criteria is a logical kind of the generic concept of "change". Unlike other classes of changes, activity ensures the realization of being in the form of the transformation of the chaos of being into the orderly self-fulfillment of the infinite and perfect being, and also the realization of the autonomous definiteness of the object of being in the corresponding environment of being.